Inventarisasi Jenis-jenis Ular ( Serpenthes ) di Kawasan Universitas Tanjungpura Pontianak - Riyandi, Rambosius, Tri Rima Setyawati, (Jurnal Protobiont, 2019)
Snakes is a Reptilian that important role in the food chains. This research was conducted in the area of Tanjungpura University, Pontianak. The aim of this research use to determine the types of snakes found and to find out the characteristics of each snake types in Tanjungpura University area Pontianak. The sampling research was done from March to May 2018, with the Visual Encounter Survey (VES) method. The results found 17 individual of 10 species, 7 families (Colubridae, Cylindrophiidae, Elapidae, Homalopsidae, Pythonidae, Typhlopidae, and Xenopeltidae). The snakes found consisted of 7 species of non- venomous snakes which included as Coelognathus flavolineatus, Cylindrophis ruffus, Homalopsis bucatta, Malayophiton reticulatus, Ptyas korros, Ramphotyphlops braminus (free-living snakes), Xenopeltis unicolor, and 3 species of poisonous snakes which included as Ahaetulla prasina, Dendrelaphis pictus, and Naja sputatrix